Meningkatkan Kualitas Penyajian Laporan Keuangan melalui Sistem Informasi Akuntansi Berbasis ERP-SAP - Ismail, Muhammad Fahreza; Sari, Nur Rahmah; Farild, Miftha (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2022)
This study aims to examine how ERP-SAP based Accounting Information Systems are able to improve the quality of financial statements at PT PLN Persero UIKL SULAWESI. This study is a qualitative study with a case study approach. The data used is primary data obtained through interviews and observation. Data analysis used data triangulation which consisted of data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Accounting Information System at PT PLN Persero UIKL SULAWESI has a major contribution to the quality of financial reporting, especially in the process of preparing and presenting financial reports. In addition, this study also found that the results of financial reporting that were input using the ERP-SAP based Accounting Information System were able to improve the quality of the financial reports by fulfilling the qualitative requirements of financial reporting and providing an integrated system that allows the central office to control data processing automatically in real time.